Contribution of hip extension and lumbar lordosis during back walkover performed by rhythmic and woman artistic gymnasts: a preliminary study - Eyssartier, C.; Poulet, Y.; Marsan, T.; Valdes-Tamayo, L.; El Oujaji, S.; Robert, M.; Billard, P.; Thoreux, P.; Sauret, C. (Computer Methods in Biomechanics and Biomedical Engineering, 2020)
Gymnastics practice necessitates a very wide range of motion of the lumbar spine, especially during back walkovers (Hall 1986). Besides, literature highlighted that simple tasks such as forward and backward bending require coordination between lumbar spine and hips movements (Lee and Wong 2002). This suggests that a back walkover, starting with a back extension enabling the gymnast to reach a bridge posture, involves a very special relationship between the lumbar spine and the hip joint of the rear leg. Rhythmic and artistic gymnasts have different approaches of performing back walkovers that are visually apparent and that suggest that rhythmic gymnasts have a more flexible spine. However, considering the close correlation between the joints movements of the spine-pelvis complex, it can be hypothesised that the hip extension may facilitate the tilt of the sacral surface and consequently, is expected to have a critical role in achieving a back walkover.